Private Practices : Harry Stack Sullivan, the Science of Homosexuality and American Liberalism. - Wake, Naoko (UPCC book collections on Project MUSE., 2011)
Private Practices examines the relationship between science, sexuality, gender, race, and culture in the making of modern America between 1920 and 1950, when contradictions among liberal intellectuals affected the rise of U.S. conservatism. Naoko Wake focuses on neo-Freudian, gay psychiatrist Harry Stack Sullivan, founder of the interpersonal theory of mental illness. She explores medical and social scientists' conflicted approach to homosexuality, particularly the views of scientists who themselves lived closeted lives. In assessing how these dynamics worked to shape each other, Priva.